Fertility-sparing approach in concurrent gliomatosis peritonei and growing teratoma syndrome in a young woman - Ahmad Nasfy, Siti Nawwal; Abdul Hamid, Habibah; Md Khairuddin, Azalea; Mohamad Fauzi, Maryam Kameelah (BMJ Publishing Group, 2024)
Gliomatosis peritonei (GP) and Growing Teratoma Syndrome (GTS) are rare and clinically significant conditions often associated with ovarian teratomas. GP involves the development of benign glial implants on the peritoneal surface, while GTS is characterised by the growth of benign, yet enlarging peritoneal implants following chemotherapy for malignant germ cell tumours. These implants are typically histologically mature teratomas devoid of malignancy. Our report documents a unique case where both GP and GTS manifested in a patient undergoing treatment for an immature ovarian teratoma. This dual occurrence is scarcely reported in the existing literature. The patient, a nulliparous woman in her 20s, developed a tumour indicative of GTS immediately after completing three cycles of bleomycin, etoposide and cisplatin therapy. This chemotherapy regimen followed fertility-sparing surgery for a stage IIIb ovarian immature teratoma. Given that total tumour resection is pivotal in positively influencing the prognosis of GTS, early minimally invasive surgical intervention before significant tumour growth is essential. This approach is particularly crucial considering that ovarian germ cell tumours are commonly present in younger patients, necessitating a focus on fertility preservation in most cases.